СРЕДНЯЯ АЗИЯ В ТВОРЧЕСТВЕ Н.С. ТИХОНОВА - Кямран Кязимов (Studia Rossica Posnaniensia)
Middle Asia holds an honorable place in the literary activity of N.S. Tikhonov, the Russian poet of the 20th century. The interest in the East brought Tikhonov to Inner Asia. With great mastership Tikhonov glorifies in his works the life, customs and the traditions of the people of Central Asia, especially those of Turkmenistan.